Biochemical factors of wound healing: prospects and limitations of application in clinical practice - Yavna, Nataliia; Turkina, Vira (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. The full-scale war in Ukraine has led to a significant number of wounded among both military personnel and civilians. Combat injuries often become chronic due to limited access to medical care and a high risk of wound infection. In addition, chronic wounds, particularly diabetic foot ulcers and venous ulcers, continue to represent a major healthcare problem because of their high prevalence. An imbalance of biochemical factors that regulate the process of wound healing at the stages of inflammation, angiogenesis, proliferation, and remodelling can contribute to the chronicity of wounds. Aim. In this review, we analyse the role of biochemical regulators at different stages of tissue repair and consider the possibilities of integrating these data into clinical practice. Materials and Methods. Approximately 50 literature sources were analysed. Articles from PubMed, Mendeley, and Europe PMC databases, as well as specialised Ukrainian journals, were used. We selected the most characteristic biochemical factors for each stage of tissue repair, as well as those with the greatest therapeutic potential. Results. The following biochemical factors were examined: haemostatic components (thrombin and fibrin), inflammatory mediators (IL-10, MMPs/TIMPs), angiogenesis and proliferation regulators (VEGF, PDGF), gasotransmitters (H₂S), and extracellular matrix components (hyaluronic acid). Each group demonstrated therapeutic potential in experimental and, to a significantly lesser extent, in clinical settings. Conclusions. However, the clinical application of these biomolecules is limited by molecular instability, dose-dependent risks, high cost, and a lack of standardisation. Therefore, optimisation of delivery systems and the conduct of high-quality clinical studies are required.